Pengembangan Aplikasi Asmaul Husna Untuk Smartphone Dengan Sistem Operasi Android - Muhammad Hery Santoso; Endang Setyawati (Media Aplikom, 2019)
The development of Information and Communication Technology is currently growing very rapidly. One of them is mobile technology. Mobile technology is currently not only used as a communication tool, but also to facilitate users in everyday life. Android is a new generation of mobile platforms. Platform that gives developers to develop what they expect. The learning media of Asmaul Husna are still dominated by books which cause people to be less interested in reading it. Therefore, researchers developed the Asmaul Husna Application Equipped with Nadhom and Prayer Based on Android as a learning medium in understanding and memorizing the Asmaul Husna that can be used anytime and anywhere. The method used to develop the Asmaul Husna Application Equipped with Nadhom and Prayer Based on Android is a Prototyping method. Performance testing of this application is based on the Dimension of Quality For Goods with the product test value (NUP), which is equal to 90.83. To test usefulness the application, researcher created a questionnaire which was then filled by 20 members of IPNU (Nahdlatul Ulama Student Association) and 30 members of IPPNU (Nahdlatul Ulama Princess Student Association) with the highest benefit test results lies in the Efficiency aspect of 93.5%.